Knowledge on and Compliance with Standard Precautions among Medical Students in Jharkhand, India: A Cross-Sectional Study - Jawanpuria, Ankita; Dash, Chinmaya (International Journal of Integrated Health Sciences, 2024)
Objective: To assess the knowledge, attitude, and compliance with standard precautions among medical students in a tertiary care hospital in Jharkhand, India.Methods: A total of 280 medical students, including phase I and phase II MBBS students, participated in the study. Phase I comprised an introduction to standard precautions in four-hour classes while the Phase II comprised of 8 hours of theory and three skill assessments on standard precautions according to the CBME curriculum and pandemic module. A structured validated questionnaire was used to collect data on the student's knowledge, attitude, and practice related to standard precautions. The questionnaire included items assessing various aspects of standard precautions, and scoring criteria were used to evaluate student performance. The overall level of knowledge, attitude, and practice was classified as poor (<50% score), moderate (50–79% score), and good (≥80% score).Results: Among the phase I students, 32.8% got a good score. In contrast, in the phase II, 56.6% demonstrated good performance in adhering to standard precautions. The median total score was 68 (interquartile range 62-71) of 85, indicating a satisfactory level of understanding and compliance with standard precautions. However, areas such as needing to remove PPE before leaving the patient's environment and not recapping needles showed rooms for improvement.Conclusion: Students showed good knowledge and compliance with standard precautions. Phase II students demonstrated a better understanding of standard precautions compared to their phase I counterparts. This highlights the positive impact of practical hands-on training as particularly emphasized in the phase II curriculum.